2019
DOI: 10.1158/1078-0432.ccr-18-2076
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated Macrophages as Prognostic and Predictive Biomarkers for Postoperative Adjuvant Chemotherapy in Patients with Stage II Colon Cancer

Abstract: Purpose: For stage II colon cancer, the efficacy of postoperative adjuvant chemotherapy remains controversial. It is well known that tumor-associated macrophages (TAMs) are important in tumor progression. In this study, TAMs were investigated as prognostic and predictive biomarkers for the efficacy of adjuvant chemotherapy for stage II colon cancer after radical resection. Experimental Design: This study enrolled two independent cohorts of consecutive patients from one medical center with pathologic stage II c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
100
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 42 publications
(51 reference statements)
7
100
0
2
Order By: Relevance
“…Classified as part of the mononuclear phagocytic system (MPS), macrophages are a group of terminally differentiated cells that play a critical role in tissue homeostasis, inflammation, and protection against pathogenic infections. As reported previously, the presence of TAM was associated with poor clinical outcome in patients with glioma, cholangiocarcinoma, ovarian, breast cancer, and Hodgkin's lymphoma [26][27]. TAMs were involved in an indirect mechanism of promoting tumorigenesis, tumor metastasis and tumor neovascularization along with the tumor-derived angiogenic factors [28].…”
Section: Discussionmentioning
confidence: 59%
“…Classified as part of the mononuclear phagocytic system (MPS), macrophages are a group of terminally differentiated cells that play a critical role in tissue homeostasis, inflammation, and protection against pathogenic infections. As reported previously, the presence of TAM was associated with poor clinical outcome in patients with glioma, cholangiocarcinoma, ovarian, breast cancer, and Hodgkin's lymphoma [26][27]. TAMs were involved in an indirect mechanism of promoting tumorigenesis, tumor metastasis and tumor neovascularization along with the tumor-derived angiogenic factors [28].…”
Section: Discussionmentioning
confidence: 59%
“…Alexander, et al Cancer Treatment Reviews 83 (2020) 101949 in immune resistance [170]. CD68 is a generic macrophage marker, whereas CD163 and CD206 are believed to be markers more specific to M2 tumour associated macrophages that have been associated with a worse outcome [171]. There were twenty-two studies overall in colon or colorectal cancer although one study had an overlapping population [172], leaving twenty-one independent studies comprising 4879 patients [60,83,85,87,89,91,96,111,122,123,168,171,[173][174][175][176][177][178][179][180][181].…”
Section: Macrophagesmentioning
confidence: 99%
“…CD68 is a generic macrophage marker, whereas CD163 and CD206 are believed to be markers more specific to M2 tumour associated macrophages that have been associated with a worse outcome [171]. There were twenty-two studies overall in colon or colorectal cancer although one study had an overlapping population [172], leaving twenty-one independent studies comprising 4879 patients [60,83,85,87,89,91,96,111,122,123,168,171,[173][174][175][176][177][178][179][180][181]. Of these, eleven studies (2038 patients) found that higher infiltration of macrophages were associated with a better prognosis [60,83,87,96,122,[175][176][177][178]180,181], compared with five studies (1965 patients) finding a worse prognosis [85,168,171,173,179].…”
Section: Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations